Pendidikan Multikultural di Indonesia dan Relevansinya dengan Konsep Islam - Nashihin Nashihin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
The purpose of this study was to determine multicultural education in Indonesia and its relevance to the concept of Islam. This type of research is a qualitative research with a library research approach which consists of two types of data, namely primary data and secondary data. Primary data were obtained using documentation techniques, namely data collected from documents in the form of books, research journals. The secondary data is in the form of magazines, articles and other scientific works that are culturally educational. The analysis technique of this writing is Content Analysis, which is data processing in a separate way related to the discussion of multicultural education which is then described, discussed and criticized. The results of the research are as follows: 1) Multicultural education has three goals that are developed for each student, namely the development of cultural identity which is a competency possessed by students, interpersonal relationships and self-empowerment; 2) The Qur'anic view on multicultural education includes at least five characters, namely learning to live in differences, building mutual trust and understanding, being open in thinking, appreciation and interdependence, as well as conflict resolution and non-violent reconciliation.